Designation of a neotype for Clorindaia hecaloides Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Faltalini) - Paradell, S.; Zahniser, J.n. (Zootaxa, 2018)
Linnavuori (1975) established the genus Clorindaia with the newly described species C. hecaloides Lv. designated as the type species of the genus. The genus currently includes five valid species, known from Brazil, Paraguay, and Argentina. C. hecaloides was described based on only one female specimen from Argentina, Formosa Prov., Clorinda. Linnavuori (1975) indicated that the holotype was deposited at the Museo de La Plata. However, extensive searches for the specimen at this institution and also at the American Museum of Natural History, at the Ohio State University Collection, and at US National Museum of Natural History have not recovered the specimen. Blocker & Fang (1992) also reported unsuccessful searches for the holotype and for a parasitized female specimen collected in Chile, reported by Linnavuori & DeLong (1977). Because the holotype appears to have been lost and because the description was based on a female which does not always provide unambiguous diagnosable characters at the species level in this group of leafhoppers, the identity of this species based on the original description unclear.